Integration of the Game "Cooking Crazy Restaurant" and Direct Practice in Cooking Learning for Latiffa Az-Zahra Kindergarten Children - Nabila; Khaira, Alesha (International Journal Education and Computer Studies (IJECS), 2024)
This innovative study investigates the synergy between digital gamification and kinesthetic pedagogy through the hybrid implementation of the educational game "Cooking Crazy Restaurant" and physical cooking practice in Latiffa Az-Zahra Kindergarten. With a mixed-methods experimental design integrating quantitative (gameplay scores, time-on-task metrics) and qualitative (semi-structured interviews, participant observation) analyses, the study uncovers the bidirectional learning transfer mechanisms between virtual competencies and real-world skills. Empirical data show a 72% increase in procedural accuracy in measuring ingredients, a 41% decrease in error rate in hygiene techniques, and an 88% achievement in retention of nutritional concepts after 8 weeks of intervention. Thematic analysis identified three pillars of success: (1) a dynamic difficulty adjustment system that creates an optimal flow state for beginners, (2) a haptic-visual synchronization mechanism that strengthens sensorimotor connections, and (3) a social learning scaffolding architecture through the co-op challenges feature. The implementation of the Phygital Pedagogy Framework model not only increased cooking self-efficacy (+54 points on the Bandura scale) but also spurred the development of 21st century skills such as critical sequencing and resource management. This finding revolutionizes the early childhood education paradigm by proving that game-technology integration is not just an entertainment tool, but a cognitive amplifier that can transform passive learning into experiential mastery.